Some factors affecting micropropagation of some wild medicinal plants 2-Achilleafragrantissima (Forssk.) SCH. BIP., plant. - Ali, M.A.M.; El-Mekawy, M. A.; Belal , A. H.; Shehata, S. A. (2006)
Culturing leaf explants of Achillea fragrantissima on Murashige and Skoog (MS) medium supplemented with 2, 4-dichlorophenoxy acetic acid (2, 4-D) at 1.0 or 2.0 mg/l resulted in high callus fresh weight after 30 and 60 days without significant differences between the two concentrations. MS medium strength at full or 1/2 strength was not significantly effective on shoots number, shoots length and number of leaves/shoot, where benzyl adenine (BA) concentration at 0.5 mg/l was enough to enhance shoots number, shoot length and leaves number/shoot. The best rooting for shoots and root length was obtained from MS 1/. strength combined with 0.1 mg/l indole-3-acetic acid (fAA). The acclimatization process of plant lets were successful on sand: peat moss medium J: J v/v with a percentage of90% survival plants.
Includes reference.
Summary in Arabic.
1
Keywords: Medicinal plants -- Breeding; Medicinal plants -- Micropropagation; Achillea